Weighted pseudoinversion of matrices with singular weights - Galba, E. F. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
Weighted pseudoinverse matrices with singular weights are represented in terms of the coefficients of characteristic polynomials of certain square matrices. By using the expression obtained, we construct limit representations of weighted pseudoinverse matrices with singular weights.